Characterizations of robust optimality conditions via image space analysis. (1st September 2020) - Ansari, Q. H.; Sharma, P. K.; Qin, X.
ABSTRACT: In this paper, we consider general scalar robust optimization problems and study the characterizations for optimality conditions in the general vector spaces where we do not require any topology on the considered space. By using the image space analysis and nonlinear separation function, we derive some necessary and sufficient optimality conditions, especially saddle point sufficient optimality conditions for scalar robust optimization problems. Moreover, we discuss the validity and effectiveness of our results for the shortest path problem.